2008
DOI: 10.1097/mcg.0b013e31803815b4
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine-associated Ring Mitosis in Liver Biopsy and Their Clinical Implications

Abstract: Colchicine is an alkaloid with antimitotic activity used to treat a variety of medical conditions. Colchicine toxicity can result in multiorgan failure and death. In recent years, the histopathologic features of colchicine toxicity in various organs that is, gastrointestinal tract, kidneys, salivary glands, muscle, and skin have been described. However, the histopathologic manifestations of colchicine in the liver have not been reported. We present the case of a 54-year-old man with transfusion acquired chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Liver biopsy in a patient with chronic hepatitis C who had been taking colchicine for more than 10 years presented with mildly elevated liver tests and loose stools revealed "ring" mitotic figures that were not present on a previous biopsy 7 years earlier when he was also taking the agent. 14 Colchicine is most toxic to highly proliferative tissues. It is unclear why ring mitoses were not initially present in this case and ours.…”
Section: Discussionmentioning
confidence: 99%
“…Liver biopsy in a patient with chronic hepatitis C who had been taking colchicine for more than 10 years presented with mildly elevated liver tests and loose stools revealed "ring" mitotic figures that were not present on a previous biopsy 7 years earlier when he was also taking the agent. 14 Colchicine is most toxic to highly proliferative tissues. It is unclear why ring mitoses were not initially present in this case and ours.…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that PBA and boric acid inhibit proliferation in cancer cell lines, including prostate cancer cells [17,19,27,56]. In addition to the known antimitotic effect of colchicine, it may cause an increase in proliferation [57]. It may be suggested that the proliferation increase in colchicine-treated LNCaP and PC3 cells might result from the compensatory effect caused by colchicine.…”
Section: Discussionmentioning
confidence: 99%
“…Although teratogenic effects have not been a fi eld problem, they may be expected as cleft palate and craniofacial and other deformities have been noted in mice (Keeler 1972). A special characteristic in humans is the presence of ring mitosis in the liver (Kamath et al 2008). Bile preferentially and urine or gastric fl uids secondarily are the preferred biological fl uids for analysis, although even vitreous humor may be used (Deveaux et al 2004;Cheze et al 2006).…”
Section: Colchicum Lmentioning
confidence: 99%